Present and future agroforestry land suitability analysis in central Portugal using multicriteria decision analysis - Quinta-Nova, L.C. (2022)
The expansion of monoculture tree plantations typically made up of pine or eucalyptus trees, is a main problem in Portugal. In recent years, monoculture plantations have spread across the country, driven by the pulp and paper industry. These are generally more susceptible to the spread of fire than mixed forests or agroforestry systems, which among other advantages, hold more water and reduces soil erosion. A diverse landscape with a mosaic of different uses and vegetation cover types provides a greater bulwark or natural barrier against large-scale and uncontrollable forest fires. The objective of this study is to determine the suitability for species cultivated in an agroforestry mode in the Pinhal Interior Sul region, as an alternative agricultural system, based on the analysis of the soil and climate limiting factors. For this purpose, the biophysical criteria determining the cultivation of common oak (Quercus robur L.), cork oak (Quercus suber L.), strawberry tree (Arbutus unedo L.), and sweet chestnut (Castanea sativa Mill.) were processed using a Geographic Information System for the present time and in the face of two future emission scenarios. The analysis was performed by the Analytical Hierarchy Process (AHP). After dividing the problem into hierarchical levels of decision-making, a pairwise comparison of criteria was performed to evaluate the weights of these criteria. The process was completed by validating the consistency of these operations. The AHP was adequate in the evaluation of the tree species’ suitability allowing the integration of different criteria. It is therefore essential to be aware of the suitability and resilience of agroforestry systems to meet the need to adapt to climate change.